SOCIAL APPROACH OF FACTOR OF HABITUS IN ALLEGIANT NOVEL - Allikathus Rizky Laily Febriyanti; Retno Budi Astuti; Erna Pranata Putri (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Novel has many aspects; one of them is the social aspect which is about how social life is described in the novel, for example a problem about gender and race. This research focused on factor of habitus that occurs in Allegiant Novel by Veronica Roth.The aim of this research is to find out the factor of habitus in Allegiant Novel by Veronica Roth. The method used in this research is a qualitative research method because all data are analyzed in the form of words and sentences. Based on the results of the above discussion, there are several characters that have factors of habitus. Several supporting factors are found to form habitus based on differences in capital and class differences. The capital differences found were economic capital, social capital, cultural capital and symbolic capital. There are also class differences which are divided into 3 classes such as upper class, small bourgeois class and popular class.